American Corn in Russia: Lessons of the People-to-People Diplomacy and Capitalism - Zhuravleva, Victoria I. (Journal of Russian American Studies, 2017)
This paper is devoted to the “corn diplomacy” in the context of Russian-American relations from the end of the 19th century to the Cold war period. The author focuses her attention on three cases dealt with the American attempts to export their corn and secrets of corn production to the Russian Empire and the Soviet Union. Thеsе thematic priorities give her the brilliant opportunity to analyze two dimensions of American messianic feelings deter- mined the stable long-term perception trends of Russia in the American society. The eco- nomic one arose from the attractive prospects of exports of goods, capital, and technologies into Russian markets (Russia was supposed to learn “the lessons of American capitalism”). The humanitarian one turned a famished and backward Russia into the object of aid from the rich and prosperous America and the Americans—into “international philanthropists”. At the same time one of the main author’s conclusions is that the “corn diplomacy” played an important role in promoting better understanding between Russian and Americans be- came the equivalent of the people-to-people diplomacy.